2014
DOI: 10.1080/19443994.2013.815688
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of photosynthetic bacteria wastewater treatment and study of microbial species diversity

Abstract: A B S T R A C TThe photosynthetic bacteria (PSB) wastewater treatment was optimized in terms of light and oxygen conditions, pH, temperature, initial PSB, and wastewater concentrations. The changes of microbial species were studied using PCR-DGGE technique. The results showed that in batch reactors the optimum conditions of PSB soybean wastewater treatment were natural light-micro oxygen, initial PSB concentration of 160 mg/L, initial wastewater concentration of 3,600 mg/L, pH of 8.0, and temperature of 30˚C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…via oxidative phosphorylation). In addition, several studies have reported faster COD removal rates aerobically when compared to their anaerobically grown PPB (both illuminated) (Lu et al, 2019a(Lu et al, , 2013(Lu et al, , 2011bMeng et al, 2020Meng et al, , 2017Wang et al, 2016;Yang et al, 2018b;Zhao and Zhang, 2014). This further points towards chemoheterotrophic growth under aerobic conditions (not necessarily of PPB in mixed cultures), as growth rates for common aerobic heterotrophs are higher when compared to those of PPB growing photoheterotrophically (maximum specific growth rate for heterotrophic biomass of 6.0 d -1 at 20 ºC (uptake rate of 8.95 d -1 assuming a yield of 0.67 g COD•g COD -1 ) (Henze et al, 1987) vs. photoheterotrophic acetic acid specific uptake rate by PPB of 2.4 g COD•g COD -1 •d -1 (20 ºC) (Puyol et al, 2017)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…via oxidative phosphorylation). In addition, several studies have reported faster COD removal rates aerobically when compared to their anaerobically grown PPB (both illuminated) (Lu et al, 2019a(Lu et al, , 2013(Lu et al, , 2011bMeng et al, 2020Meng et al, , 2017Wang et al, 2016;Yang et al, 2018b;Zhao and Zhang, 2014). This further points towards chemoheterotrophic growth under aerobic conditions (not necessarily of PPB in mixed cultures), as growth rates for common aerobic heterotrophs are higher when compared to those of PPB growing photoheterotrophically (maximum specific growth rate for heterotrophic biomass of 6.0 d -1 at 20 ºC (uptake rate of 8.95 d -1 assuming a yield of 0.67 g COD•g COD -1 ) (Henze et al, 1987) vs. photoheterotrophic acetic acid specific uptake rate by PPB of 2.4 g COD•g COD -1 •d -1 (20 ºC) (Puyol et al, 2017)).…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies reporting the microbial communities, batch tests (with durations of 3-4 days) have shown that aerobic heterotrophs (e.g. Pseudomonas or Hyphomonas) are present at considerable proportions at t end under illuminated-aerated conditions (Yang et al, 2018c(Yang et al, , 2018aZhou et al, 2015), and that the PPB diversity is reduced (Zhao and Zhang, 2014). In addition, the presence of strict anaerobes at the end of batches suggests that anaerobic regions might have existed in the reactors despite aeration (Peng et al, 2018;Yang et al, 2018c).…”
Section: Introductionmentioning
confidence: 99%
“…Strain 1 and Strain 5 were both identified as Bacillus sp. (Zhao et al, 2010). Fang (2008) screened and isolated thirty-seven strains from soil and active sludge, including twelve bacteria stains, eleven mildew strains, seven epiphyte stains and seven actinomyces stains.…”
Section: Screening Of Flocculant Producing Bacteriummentioning
confidence: 99%